Virtualization of social and civic activities – opportunities and threats – on the example of the Congress of People with Disabilities - Głąb, Zbigniew (Virtualizing the lives of people with disabilities, 2021)
The limitation of direct contacts resulting from the COVID-19 pandemic caused many projects – wanting to maintain their continuity – to move to the Internet. One of them is the Congress of People with Disabilities – a cyclical social initiative involving and connecting people and institutions related to the subject of disability – aimed at introducing changes and new solutions in this area. The study aimed to determine how the Congress changed its nature as a result of its transfer to the Web, as well as the opportunities, challenges and threats associated with it. The analysis takes the perspective of the social movement and the related issue of representation – taking into account the difficulties in applying this theory to the disability community in general. For the analysis, 8 free directed interviews were conducted with the organizers of the Congress and the accompanying conventions – experts (with and without disabilities) in the field of disability, involved in the organization of Congress 2020. The research results indicate a noticeable change in the nature of the Congress – especially to the social aspect associated with the relations and bonds between participants. Among the most important concerns was maintaining the rank of the Congress as an event that stands out and attracts new people to the emerging nucleus of the representation of people with disabilities in Poland. The particularly emphasized advantages of virtualization include the equalization of accessibility for people with various disabilities.